Marketing plan of the Hotel G for 2024 - Xiuqin Guo (2023)
Hotel G is a commercial economy hotel in Shanghai, established in 2019. The main income of Hotel G is from people coming to Shanghai for exhibitions and concerts within 5 kilometers around the hotel. In view of the short period of hotel operation and the fact that most of the time is in the stage of COVID-19 epidemic from 2020 to 2023, it is now facing a challenge of off-season and peak season sales and competitor with similar functions issues. The aim of this project is to design the 2024 marketing plan of Hotel G by proposing the policies of marketing-mix to face the market changes in post-COVID period. Its main objectives are to improve service quality, increase customer satisfaction and loyalty, dig deep into old customers, acquire new customers, expand business scope and increase marginal revenue in order to cope with the low income period during non-exhibition and industry off-season. After an in-depth analysis of the internal, external and competitive environment, the objectives are defined and the marketing plan is designed.